Unified Protocol Transdiagnostic Treatment in Group Format: A Preliminary Investigation With Anxious Individuals. (March 2017) - Laposa, Judith M.; Mancuso, Enza; Abraham, Gaby; Loli-Dano, Laura
Barlow et al. published the unified protocol (UP) for transdiagnostic treatment of emotional disorders, focusing on common pathological factors across a variety of diagnoses. The limited UP research to date suggests that this treatment may be particularly useful for anxiety disorders. However, it has largely been evaluated only in individual treatment format. The current study examined the effectiveness of the UP treatment in a group format, with individuals with comorbid anxiety disorder symptoms. Twenty-six individuals with clinically significant anxiety symptoms in at least two of the following areas, social anxiety, worry, or panic, participated in a 14-week manualized group treatment using the UP. Significant decreases were found on general anxiety, worry, social anxiety, panic, depression, and negative affect, and increases on positive affect. The UP may hold promise for a transdiagnostic group treatment of comorbid anxiety symptoms, but further examination of this treatment is warranted.